Is Assessment for Learning Really Assessment? - Brown, Gavin T. L. (Frontiers in Education, 2019)
This opinion piece questions the legitimacy of treating assessment for learning (AfL) as assessment. The distinction between testing and assessment is first made, then the defining characteristics of contemporary AfL are identified. While AfL claims to be assessment, my analysis argues that AfL is a pedagogical curriculum approach that has some process aspects of assessment. However, because of the interactive and in-the-moment characteristics of AfL, it fails to meet requirements of an assessment. Specifically, because the in-the-moment and on-the-fly aspects of effective classroom discussions and providing feedback happen in ephemeral contexts it is not possible to scrutinise the interpretations teachers make of student products and processes. Furthermore, we cannot know if those interpretations were sufficiently accurate to guide classroom interactions. Without social or statistical moderation, stakeholders cannot be assured that valid conclusions are reached. Additionally, the scale of error in both teacher and student judgment means that AfL practices cannot be relied upon for decision making beyond curriculum-embedded actions within a pedagogical process. Because teaching requires robust evidence to support decisions made about students and teachers, the practices commonly associated with AfL cannot provide sufficient evidence on which to base anything more than teaching interactions.